PENERAPAN TEKNIK PROYEKTIF DRAWING DALAM BIMBINGAN KLASIKAL UNTUK MENINGKATKAN KEMAMPUAN MANAJEMEN EMOSI SISWA KELAS X-5 SMA NEGERI 2 KEDIRI - Brilliance Titisari; Nora Yuniar Setyaputri; Luwi Adi Basuki (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Emotional management skills are crucial in shaping students’ social-emotional development, yet many still experience difficulties in recognizing, understanding, and regulating their emotions effectively. This study aims to improve students’ emotional management through the application of the projective drawing technique in classical guidance services. The research employed Classroom Action Research (CAR) involving 40 tenth-grade students (16 males and 24 females) at SMA Negeri 2 Kediri. The study was conducted in two cycles, each consisting of planning, implementation, observation, and reflection. Data were collected using an emotional management scale, observation sheets, and student worksheets (LKPD). The findings revealed a consistent improvement in students’ emotional management skills, with average achievement increasing from 52% in the pre-cycle, to 62% in the first cycle, and 72% in the second cycle. Beyond statistical results, positive changes were also observed in classroom interactions, where students became more expressive, open, and able to regulate their emotions constructively. The study concludes that the projective drawing technique is effective in enhancing students’ emotional management and may serve as an alternative strategy for school counselors in developing innovative guidance practices.